Ruang Bangsa dan Ruang Alternatif dalam Novel “Lingkar Tanah Lingkar Air” Karya Ahmad Tohari - Ricky Yudhistira Nasution; Arie Azhari Nasution; Evi Marlina Harahap (Aksara, 2022)
This research aims to discover the nation space construction and the alternative space that Ahmad Tohari offers in the novel “Lingkar Tanah Lingkar Air”. Theory used in this research is the politics of postcolonial space by Sara Upstone (2009), particularly at the level of nation space which has basic structure of space, place, overwriting, (b)order, chaos and post-space. The theory and problem selection in this research are related to the phenomenon of the re-emergence of separatist groups in Indonesia. In this research, the method used is qualitative descriptive. The result of the research indicates that the construction of nation space in LTLA novel have the form of Republic with a presidential system of government in which there are place and (b)order that still inherit the colonial space construction. The nation space of Indonesia demand for homogeneity, stability, constancy and fixed, consequently bring up the groups that against the State. Meanwhile, the alternative space offered by Ahmad Tohari is "coming home" which can be mobilized to several meanings. Firstly, Tohari provides an alternative space for returning to Republic of Indonesia by accepting all (b)orders that have been constructed and jointly building the nation space without rising a ceasefire among Indonesians. Secondly, an alternative space for returning to our hometown, our house, our parents and own ourselves. Finally, an alternative space for returning to a transcendent dimension and the God by choosing to be martyred by the State. AbstrakPenelitian ini bertujuan untuk membongkar konstruksi ruang bangsa dan menemukan ruang alternatif yang ditawarkan pengarang dalam novel “Lingkar Tanah Lingkar Air” karya Ahmad Tohari. Teori yang digunakan adalah politik ruang pascakolonial yang digagas oleh Sara Upstone (2009), khususnya pada level ruang bangsa yang memiliki struktur dasar space, place, overwriting, (b)order, chaos, dan post-space. Pemilihan masalah dan teori dalam penelitian ini berkaitan dengan fenomena munculnya kembali kelompok-kelompok separatis di Indonesia. Adapun metode yang digunakan adalah metode penelitian deskriptif kualitatif. Hasil penelitian menunjukkan bahwa konstruksi ruang bangsa dalam novel LTLA berbentuk Republik dengan sistem pemerintahan presidensial, yang di dalamnya terdapat place dan (b)order yang masih mewarisi konstruksi ruang kolonial. Ruang bangsa Indonesia yang demikian menuntut adanya homogenitas, kestabilan, keajegan, dan fixed, yang karenanya memunculkan kelompok-kelompok yang membelot pada negara. Sementara itu, ruang alternatif yang ditawarkan oleh Ahmad Tohari adalah “Pulang”, yang dapat dimobilisasi ke beberapa makna. Pertama, Tohari memberikan ruang alternatif untuk pulang ke Republik Indonesia dengan menerima segala (b)order yang telah dikonstruksi dan bersama membangun ruang bangsa tanpa memunculkan gencatan senjata sesama bangsa Indonesia. Kedua, ruang alternatif untuk pulang ke kampung halaman, ke ruang rumah, pulang ke orang tua, dan pulang ke diri sendiri. Ketiga, ruang alternatif untuk pulang ke dimensi transenden, ke Sang Pencipta, dengan jalan syahid membela negara.